An investigation of the polarisation dependence of insect radar cross sections at constant aspect - Aldhous, Anthony C. (Cranfield University, 1989)
A low cost system for measuring insect radar cross section (RCS) as a function of polarisation orientation when viewed at constant vertical aspect is presented. A low power continuous wave system (frequency 9.4 GHz) was developed which illuminated a target vertically and measured the power reflected back as the target was rotated in the horizontal plane. Data was collected by a microcomputer and stored on floppy disk for later analysis. A standard target was measured before each insect target and software used this data to calibrate the system for each insect target measurement. A 5 parameter mathematical model, based on the scattering matrix, is described. Software was developed to calculate the parameters from collected data using a least squares procedure. Measurements from 54 specimens representing 18 species of commonly available insect are reported. Average RCS’s were similar to the RCS of water spheres of equivalent mass. For small insects, the maximum and minimum RCS occurred when the electric vector (E-vector) was parallel and perpendicular to the body axis respectively. As insect size increased, a subsidiary maximum developed when the E-vector was perpendicular to the body axis, becoming dominant for the largest insects measured. The shapes of the RCS pattern were approximately ‘mirror’ symmetric, except for the RCS curves from S. gregaria, the largest insects measured, which were asymmetrical and sensitive to the position of the large rear legs. It was found that the ratio of maximum RCS to minimum RCS bore no simple relationship to the ratio of body length to abdomen width of the insect, even when adjusted for mass and was not a useful measure of target shape. The implications of this data are discussed and suggestions for further work are presented.